Fixed-bed and simulated moving bed chromatography using achiral and chiral adsorbents for the complete preparative separation of a quaternary mixture - Arafah, Rami (2022)
Nadolol is a nonselective beta-adrenergic receptor antagonist (beta-blocker) pharmaceutical drug, widely used in the treatment of cardiovascular diseases, such as hypertension, ischemic heart disease (angina pectoris), congestive heart failure and certain arrhythmias. This drug is still being marketed as a mixture of four stereoisomers in spite of the clear evidences that only one of its four stereoisomers has the desired therapeutic effect. Preparative liquid chromatography is actually an accepted route in industry to obtain enantiomeric pure drugs. Today, the combining of different chromatographic technologies, such as fixed-bed and simulated moving bed together with the use of achiral and/or chiral adsorbents are an important improvement in performance of preparative separation of multicomponent chiral drugs into its single pure stereoisomers. This work confirms this improvement using the referred strategy with mobile phase composition optimization at both normal and reversed-phase mode. Different separation strategies were designed and optimized, enlarging the packing materials possibilities, from fully chiral (Chiralpak) to achiral (C18) combined with chiral separation. For each separation step, the optimization of the solvent composition was carried out with pure alcohol, alcohol-hydrocarbon and alcohol-water mixtures, all with a basic modifier (diethylamine), taking into account the strong basic nature of the nadolol.